1986
DOI: 10.1002/gps.930010105
|View full text |Cite
|
Sign up to set email alerts
|

The prescription of psychotropic medication in local authority old people's homes

Abstract: 22% of the elderly residents of the 12 local authority homes in one London borough were being prescribed major tranquillisers (neuroleptic) medication. Standard diagnoses of severe dementia and of depression in residents without severe dementia were associated with this prescription as was a report by the Head of Home that the resident wandent wandered and was suspicious. These findings suggested that some non ‐ demented residents who display disturbed behaviour are being prescribed this medication, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
10
1

Year Published

1988
1988
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
6
10
1
Order By: Relevance
“…These findings are in accordance with other reports (Mann et al, 1986;Gilleard et al, 1983;Dehlin and FranzCn, 1985), and neuroleptic medications have become a mainstay in the treatment of the agitated elderly demented patient (Risse and Barnes, 1986). However, their usefulness has been questioned (Barnes et al, 1982;Findlay et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with other reports (Mann et al, 1986;Gilleard et al, 1983;Dehlin and FranzCn, 1985), and neuroleptic medications have become a mainstay in the treatment of the agitated elderly demented patient (Risse and Barnes, 1986). However, their usefulness has been questioned (Barnes et al, 1982;Findlay et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…Both shortly after admission and 6 months later, neuroleptics are the most frequently taken drug classes, which is in accordance with the data of authors using a point-prevalence design (e.g. Mann et al 1984Mann et al , 1986Burns et al 1988;Beardsly et al 1989). To our knowledge, no authors investigating psychotropic drug intake shortly after admission have compared different types of psychotropics.…”
Section: Discussionsupporting
confidence: 71%
“…We found that this scale did not give a proper picture of what happened in patients suffering from both physical and psychiatric disorders (centres I and 3). On the whole our results are in good agreement with those o f other studies (6,7). The main indications for psychotropic medications are behavioural disturbances that created social problems, particularly in patients with senile dementia.…”
Section: Discussionsupporting
confidence: 95%